Socio-economic impact of alternative spectrum assignment approaches in Latin America - Raul Luciano Katz; Fernando Beltrán (International Telecommunications Society (ITS), 2015)
The essential input to the exploitation of mobile broadband known as radio spectrum is a scarce resource, whose allocation and eventual assignment by telecommunications regulator and spectrum authorities across the world is of outmost importance. The most popular approach to spectrum assignment is to run an auction where frequency bands get assigned over a fairly large time horizon; this feature of spectrum assignment plays a role in shaping the mobile telecommunications markets and may foreclose the emergence of alternative, plausibly more efficient, new modes of spectrum utilization. This paper's objective is to demonstrate that conventional spectrum assignment processes (based on auctioning of single use licenses) can be enriched with other approaches, such as reserving portion of spectrum to unlicensed use. The methodology explores alternative spectrum assignment scenarios (fully based on licenses and mixed) for a Latin American country, and quantifying their impact in terms of achieving coverage in rural and isolated areas, as well as promoting technological innovation.
Keywords: 330; Mobile broadband; Spectrum; Latin America; Rural coverage